Synthesis, Characterization, and Measurement of New 1144‐Type Iron‐Based Superconductors: A Systematic Review - Gedefaw Mebratie; Tamiru Negussie; Gebregziabher Kahsay (Nano Select)
ABSTRACT The newly discovered 1144‐type iron‐based superconductors (FeBSCs) are hybrids of the same two 122‐type structures. The novel 1144‐type FeBSCs were synthesized with a superconducting transition temperature ranging from 31 to 37 K. This study systematically investigates the current findings and future possibilities of EuRbFe4As4, EuCsFe4As4, CaRbFe4As4, and CaKFe4As4 FeBSCs since they have high upper critical magnetic field, high critical current density and low anisotropy, strong vortex pinning properties. The current review article gives a brief explanation on the crystal structure, electronic structure, band gap, magnetic properties, superconductivity, pairing mechanism, synthesis methods, characterization, and measuring mechanisms of the selected novel 1144‐type FeBSCs.